Strategic Manajement Education Based Customers - Dasor, Yohanes Wendelinus (Jurnal Pendidikan dan Kebudayaan Missio, 2016)
A phenomenon indicates that college graduates steadily increase every year. The increasing number is not in line with the availability of employment.Moreover, Indonesian education institutions have not prepared their graduates for work. In thiscase, there is a mismatch between the college outputs, the demand of economic development , and thequality of graduates under the demand of job requirement . Based on the phenomenon, educationalinstitutions should be handled by customer-based management concept. Customer-based education managementis the management of educational institutionwhich producesoutputs for the satisfaction of customers.Some characteristics educational outputs are intelligent, skilled and humane.For the sake of that,the educational intitutions must consider the quality of education strategic manajement including themanajement of cognitive and skill. By this way, educational outputs can meet the demand of customers.Keywords: manajement, strategic, education, customers